PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATA PELAJARAN BAHASA INDONESIA KELAS IV SEKOLAH DASAR - Muna, Lailatul; Mujianto, Gigit (Academy of Education Journal, 2023)
The low learning outcomes of class IV narrative text material make learning ineffective. The research objective is to improve student learning outcomes. The research was carried out in two cycles with the PBL (Problem Based Learning) model, in early learning the average value was 75, increased by 81 in cycle I, and Cycle II increased by 93. The percentage of completeness in early learning was 50% then in Cycle I it increased by 70 %, and Cycle II rose 95%. The percentage of incompleteness before the cycle was 50%, then Cycle I decreased by 30%, and Cycle II decreased again by 5%. The conclusion of the application of the PBL model is able to improve learning outcomes in Indonesian language class IV at SDN 02 Girimoyo, Malang Regency.